2017
DOI: 10.3811/jjmf.31.152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluid Properties on Countercurrent Flow Limitation in Vertical Pipes

Abstract: To evaluate effects of the diameter on countercurrent flow limitation (CCFL) in vertical pipes, in our previous study, we classified CCFL into CCFL-L at the sharp-edged lower end, CCFL-U at the sharp-edged upper end, and CCFL-P inside the vertical pipe with round-edged upper and lower ends, and we found that the characteristic length in the Wallis parameter,(where D and L respectively denote the diameter and the Laplace capillary length), is respectively β = 0, 1 and β ≈ 0.5 for CCFL-L, CCFL-U and CCFL-P. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Wallis [15] showed that the liquid viscosity (which is not included in (1)-(4)) affects CCFL and he used the dimensionless viscosity number. We (Murase et al [24]) used the viscosity ratio of the gas and liquid phases for CCFL-L, CCFL-U, and CCFL-P, but Ilyukhin et al [18,19] used the density ratio of the gas and liquid phases for CCFL with the protruding top and bottom ends. Therefore, CCFL correlations, which include effects of fluid properties, should be carefully used considering the application range.…”
Section: Discussionmentioning
confidence: 99%
“…Wallis [15] showed that the liquid viscosity (which is not included in (1)-(4)) affects CCFL and he used the dimensionless viscosity number. We (Murase et al [24]) used the viscosity ratio of the gas and liquid phases for CCFL-L, CCFL-U, and CCFL-P, but Ilyukhin et al [18,19] used the density ratio of the gas and liquid phases for CCFL with the protruding top and bottom ends. Therefore, CCFL correlations, which include effects of fluid properties, should be carefully used considering the application range.…”
Section: Discussionmentioning
confidence: 99%